Proposal of psychological preparation in artistic gymnastics - Miltiadis, P.; Fotios, M.; Michalis, P. (Science of Gymnastics Journal, 2012)
The athletes` psychological preparation constitutes part of the whole athletic preparation. However, the implementation of psychological skills training programs to gymnasts is rather limited and has a vague outcome. The purpose of the present paper was to make a proposal with the aim to assist the development of psychological skills training programs in artistic gymnastics. This proposal maintains that such a program should have the following objectives: (1) reinforcement of inner motives, such as volition, (2) avoidance of negative feelings, such as fear, and (3) implementation of a series of other practices discussed in the paper.